Biomechanics and predicted energetics of sprinting on sand: Hints for soccer training - Gaudino, P.; Gaudino, C.; Alberti, G.; Minetti, A. E. (Journal of Science and Medicine in Sport, 2013)
Objectives The purpose of this study was to analyse energetic and biomechanical parameters of sprinting on sand surface, aimed at the evaluation of inherent aspects of soccer training programs, injury prevention and recovery processes. Design Twenty-nine professional soccer players took part in this study: they performed maximal sprints and maximal shuttle sprints on a 12 m distance on natural grass, artificial turf and soft, dry sand. Methods Speed, acceleration, deceleration, stride length, stride frequency, flight and contact time, estimated energy cost, metabolic and mechanical power, efficiency and stiffness values, have been calculated through the instrument SPI-Pro (GPSports, Canberra, Australia) supported by two fixed cameras. Results The comparison between values recorded on sand with those recorded on natural or artificial grass has highlighted significant decreases (p < 0.001) of speed, acceleration, stride length, flight time and mechanical power, efficiency and stiffness. Contact time, energy cost, metabolic power (p < 0.001) and deceleration (p < 0.05) were higher on sand whereas no significant differences were found regarding stride frequency (p > 0.05). Conclusions These results show that on sand it is possible to perform maximal intensity sprints with higher energy expenditure and metabolic power values, without reaching maximum speed and with smaller impact shocks. Furthermore, exercises with change of direction carried out on this surface allow to reach higher deceleration values. In addition, sprinting on sand potentially entails a limited stretch of the involved muscles. It can therefore offer a valid alternative to traditional training, injury prevention and rehabilitation programs.